ANALISIS HUKUM ISLAM TERHADAP PERBEDAAN PEMAHAMAN TENTANG NIKAH KEKERABATAN - Nilhakim (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2021)
The purpose of this research is to know how the concept of kinship marriage in Islamic law. The research method used is the content analysis method, with the primary source being the source of Islamic law (hadith) regarding the prohibition of marrying a woman who is still a family relationship. analysis steps, namely: first, formulate the problem to be studied. Second, the author determines the authenticity of the hadith as a source of Islamic law. Furthermore, in the third step, the author categorizes the views of the ulama on the argument of the hadith regarding the prohibition of marrying a woman who is still a family relationship. Furthermore, the data is described. The trick is to compare the opinions of the scholars about the hadith prohibiting marriage with women who are still related to the family. The results showed that, the prohibition of marrying a woman who is still a family relationship, the textual text of the original law is that it is permissible to marry her.